Thariqah-Based Neck Exercise Program Reduces Headache Intensity Among Indonesian College Students - Sukarmin Sukarmin; Elly Nurachmah; Sri Yona; Dewi Gayatri; Nana Rochana (Nurse Media: Journal of Nursing, 2025)
Background: Headaches are common among students due to academic stress and poor sleep habits. One way to reduce headaches is through neck exercises using Thariqah movements. Previous studies have focused only on physical neck exercises, yet a more holistic approach by combining dzikr (Laa ilaha ilallah) recited Thariqah movements with the exercises has never been studied.